EFEKTIVITAS OZONATED VIRGIN COCONUT OIL TERHADAP PENYEMBUHAN LUKA FULL- THICKNESS SKIN DEFECT PADA TIKUS SPRAGUE DAWLEY - Surbakti, Herry Maha Putra; Yuniati, Renni; Handojo, Djoko (Medica Hospitalia : Journal of Clinical Medicine, 2021)
AbstractIntroduction: Wounds are a breakdown of tissue integrity / continuity that can lead to infection. Virgin Coconut Oil is a processed coconut product made by processing fresh coconut flesh at low temperature and has a high nutritional content. Ozone therapy is an alternative therapy that has disinfectant properties and can induce strong oxidative stress. Methods: This study was conducted on 50 Sprague-Dawley rats that had injuries. We performed full thickness wounds and administered ozonated doses of VCO to mice. We looked at shrinkage of wounds and TGF Beta levels in mice. Assessment was carried out on day 7 and day 14 to assess the wound and TGF-beta immunohistochemically. Results: There was a significant difference in the wound shrinkage variable between the negative control group and the group that received VCO offerings both on day 7 and day 14. We also found a significant difference in the TGF-beta variable between the negative control group and the group that received VCO offerings both on day 7 and day 14. Conclusion: The administration of ozonated virgin coconut oil was effective in increasing the expression of TGF-? in the full thickness defect of Sprague Dawley rats and was effective in increasing the reduction in wound size in the full thickness defect of Sprague Dawley rats.